2005
DOI: 10.1165/rcmb.2005-0046oc
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Calpain-Calpastatin in Cigarette Smoke–Induced Inhibition of Lung Endothelial Nitric Oxide Synthase

Abstract: We reported that cigarette smoke extract (CSE) causes decreases in the activity and expression of endothelial nitric oxide synthase (eNOS) and calpain activity in pulmonary artery endothelial cells (PAECs). Calpains are a family of calcium-dependent endopeptidases, and their specific endogenous inhibitor is calpastatin. In this study, we evaluated the role of calpain-calpastatin in CSE-induced decrease in eNOS gene expression. PAEC were incubated with 5-10% CSE for 2-24 h. eNOS gene transcription rate, eNOS me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…However, infection of PAEC with adenovirus containing a fulllength calpastatin cDNA resulted in a dramatic decrease in calpain activity as measured by detecting calcium-dependent cleavage of resorufin-labeled casein in vitro and the calpain-mediated degradation of natural substrate spectrin in intact cells. However, the protein contents of calpain-1 and calpain-2 did not change in calpastatin-overexpressed cells, suggesting that the decrease in calpain activity is caused by the inhibitory effect of calpastatin on calpain (27). Corresponding to the changes in calpain activity, infection of PMEC with adenovirus containing full-length porcine calpastatin cDNA caused decreases in endothelial monolayer wound repair and endothelial tube formation as well as in VEGF-induced increases in monolayer wound repair and tube formation (Fig.…”
Section: Effect Of Calpastatin Overexpression On Calpain Activity Enmentioning
confidence: 92%
See 1 more Smart Citation
“…However, infection of PAEC with adenovirus containing a fulllength calpastatin cDNA resulted in a dramatic decrease in calpain activity as measured by detecting calcium-dependent cleavage of resorufin-labeled casein in vitro and the calpain-mediated degradation of natural substrate spectrin in intact cells. However, the protein contents of calpain-1 and calpain-2 did not change in calpastatin-overexpressed cells, suggesting that the decrease in calpain activity is caused by the inhibitory effect of calpastatin on calpain (27). Corresponding to the changes in calpain activity, infection of PMEC with adenovirus containing full-length porcine calpastatin cDNA caused decreases in endothelial monolayer wound repair and endothelial tube formation as well as in VEGF-induced increases in monolayer wound repair and tube formation (Fig.…”
Section: Effect Of Calpastatin Overexpression On Calpain Activity Enmentioning
confidence: 92%
“…The inserts excised from NheI/SalI sites of calpastatin-CFP were used to construct recombinant adenoviruses containing tetracycline (Tet) -regulated gene inserts according to the manufacturer's instructions. After package, propagation, pu-rification, and titration, the resulting adenoviruses and Adeno-X Tet-Off regulatory virus were used to coinfect PMEC as previously reported by us (27).…”
Section: Construction and Transient Expression Of An Adenoviral Vectomentioning
confidence: 99%
“…Our fi ndings of reduced eNOS expression and activity in the human vascular endothelium aft er exposure to SHS concur with previous reports of reduced eNOS protein and mRNA expression and its enzymatic activity after prolonged exposure to cigarette smoke extract in vitro. 24,25 Th us, direct characterization of the vascular endothelium may refl ect more accurately the extent of reduced NO availability in passive smokers than indirect assessment of endothelial function by FMD.…”
Section: Figure 1 -Expression Of Markers Of Endothelial Reactivity Imentioning
confidence: 99%
“…Notably, calpain inhibition affects vascular constriction and relaxation of pulmonary arteries. For example, we have previously reported that calpain inhibitors decrease gene expression of eNOS (57).…”
Section: Figure 10mentioning
confidence: 99%